2014
DOI: 10.1017/s1368980014002833
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the water, energy, pesticide and fertilizer usage for the production of foods consumed by different dietary types in California

Abstract: Consuming a more plant-based diet could to an extent alleviate the negative environmental impacts related to food production. As a method to feed ourselves more sustainably, behavioural adjustments appear to be a very important tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…We used the index of adherence to the MedDiet proposed by Trichopoulou et al (29) because it is largely used in nutritional public health studies and because its validity has been previously checked (53,54) . It has been reported that a vegetarian or vegan diet could be more environmentally advantageous than other diets which include animal products (20,55) and that a reduction in meat consumption would ease pressure on footprints (56) . Thus, a shift, even a gentle and moderate shift to less animalbased and more plant-based diets, like the MedDiet or the pro-vegetarian diet, may be positive not only for reducing all-cause mortality (57) but also for the environment (17,18,20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the index of adherence to the MedDiet proposed by Trichopoulou et al (29) because it is largely used in nutritional public health studies and because its validity has been previously checked (53,54) . It has been reported that a vegetarian or vegan diet could be more environmentally advantageous than other diets which include animal products (20,55) and that a reduction in meat consumption would ease pressure on footprints (56) . Thus, a shift, even a gentle and moderate shift to less animalbased and more plant-based diets, like the MedDiet or the pro-vegetarian diet, may be positive not only for reducing all-cause mortality (57) but also for the environment (17,18,20) .…”
Section: Discussionmentioning
confidence: 99%
“…From a health point of view, moving to diets with fewer animal-based foods would be beneficial (55,(60)(61)(62)(63) . However, some have suggested that diets based exclusively on plant products are not as healthy as others that include small amounts of animal foods, like the Mediterranean (64) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the vast majority of PD patients have no such acute exposure. Although it is difficult to demonstrate direct adverse effects of environmental toxins on humans in epidemiological studies because of various confounding factors, humans are inevitably exposed to small doses of pesticides over their lifetime9394. It is unclear what cumulative effects these pesticides pose in causing PD, especially in a genetically susceptible human.…”
Section: Discussionmentioning
confidence: 99%
“…Not all studies of sustainable diets include seafood (see, e.g., Brunelle, Dumas, & Souty, 2014;Doran-Browne, Eckard, Behrendt, & Kingwell, 2015;Erb et al, 2016;Goldstein, Hansen, Gjerris, Laurent, & Birkved, 2016;Kernebeek, Oosting, Feskens, Gerber, & Boer, 2014;Marlow, Harwatt, Soret, & Sabaté, 2015;Raphaely & Marinova, 2014;Reisch et al, 2013;Sabaté, Sranacharoenpong, Harwatt, Wien, & Soret, 2015;Temme et al, 2013). The reasons behind the exclusion were…”
Section: Barriers and Opportunities To Incorporating Seafood Into Smentioning
confidence: 99%
“…not always clear; however, a lack of data was cited (e.g., Marlow et al, 2015). A number of studies that did include seafood were also limited by lack of relevant data in standard food databases.…”
Section: Theme Sourcementioning
confidence: 99%